Independent and combined effects of handgrip strength and adherence to a Mediterranean diet on blood pressure in Chilean children (2019)
Objective: The aim of the study was to examine the combined associations between handgrip strength (HGS) and adherence to a Mediterranean diet with blood pressure (BP) in Chilean children. Methods: This cross-sectional study enrolled 1140 children (794 boys and 346 girls) 8 to 12 y of age. HGS was measured using a hand dynamometer with an adjustable grip. Adherence to a Mediterranean diet was assessed with the Kidmed score. Resting BP was measured by an automated monitor using an appropriately sized cuff. Elevated BP was defined as ?90th percentile, and high HGS was defined as sex- and age-specific normative ?80th percentile for the HGS. Results: The prevalence of elevated systolic BP, diastolic BP, and overall BP were 16.6%, 12.9%, and 8.1%, respectively. HGS was negatively associated with BP parameters in an unadjusted and adjusted model after considering potential confounders (age, sex, body mass index z-score, and HGS). Regarding diet adherence, the unadjusted model reveals that children with high adherence to the Mediterranean diet showed lower BP levels (systolic, diastolic, and mean arterial pressure) compared with children with low–medium adherence; however, these differences disappear after considering potential confounders. The combination of high HGS and optimal adherence to a Mediterranean diet was negatively associated with BP. Conclusions: Children with a high HGS levels (i.e., ?80th percentile) may somewhat overcome the deleterious effects of low adherence to a Mediterranean diet. Therefore, these findings suggest that the combination of these two components of a healthy lifestyle, especially HGS may be beneficial to children's BP. © 2018 Elsevier Ltd